2015
DOI: 10.1111/ajr.12256
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of the application and pharmacology of ethnomedicines of Indigenous Australians

Abstract: Some Indigenous Australians continue to use traditional medicines. We have tabulated these according to ailment, and have listed pharmacological actions where known. What is not known, however, is their potential to interact with pharmaceutical drugs. Further study in this area is needed to optimise health outcomes for Indigenous Australians, especially those in remote communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Lemon aspen was reported to contain a noticeable amount of both lipophilic and hydrophilic antioxidants including tocopherols and phenolics whereas native currant was found to have a significant amount of anthocyanins. 56 For the first time, Konczak et al reported higher ORAC (oxygen radical absorbance capacity – 28.8%) for lipophilic antioxidants (ORAC-L) in lemon aspen compared to other Australian citruses. 45 In addition, the same group reported a lower FRAP (ferric reducing antioxidant power – 14.0 ± 2.4 Fe 2+ per gFW) and a higher ORAC (132 ± 11.4 μmol TEq per gFW) for hydrophilic compounds (ORAC-H) in lemon aspen, compared to other native Australian fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Lemon aspen was reported to contain a noticeable amount of both lipophilic and hydrophilic antioxidants including tocopherols and phenolics whereas native currant was found to have a significant amount of anthocyanins. 56 For the first time, Konczak et al reported higher ORAC (oxygen radical absorbance capacity – 28.8%) for lipophilic antioxidants (ORAC-L) in lemon aspen compared to other Australian citruses. 45 In addition, the same group reported a lower FRAP (ferric reducing antioxidant power – 14.0 ± 2.4 Fe 2+ per gFW) and a higher ORAC (132 ± 11.4 μmol TEq per gFW) for hydrophilic compounds (ORAC-H) in lemon aspen, compared to other native Australian fruits.…”
Section: Resultsmentioning
confidence: 99%